Estimasi Kandungan Karbon dan Serapan Karbon pada Daun, Akar dan Tanah di Pesisir Mangrove Sinjai Utara Kabupaten Sinjai : Estimation of Carbon Content and Carbon Uptake in Leaves, Roots and Soil in the Mangrove Coast of North Sinjai, Sinjai Regency - Mutahharah, Mutahharah; Alamsyah, Ridha; Azizah, Rahmah; Akram, Akram (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2024)
Mangrove forests are one of the coastal ecosystems of tropical waters that have various potential benefits for both the environment and humans. The existence of mangrove forests is very necessary for the future of the earth. Mangrove forests have one very important function, namely as an absorber and store of carbon (C). Mangrove forests can store more than three times the average carbon storage per hectare by tropical land forests. This study aims to determine the carbon content and carbon absorption in leaves, roots and soil on the mangrove coast, especially in North Sinjai, Sinjai Regency. The method used in this study is the sampling method to measure the carbon content in leaves, roots and soil. The analysis will involve direct measurements in the field and laboratory analysis to obtain accurate data. The carbon content in mangrove leaves ranges from 0.9-0.11 tons/ha, with a carbon absorption capacity of 0.33-0.42 tons/ha. In the roots, the carbon content ranges from 0.44-0.72 tons/ha with an absorption capacity of 1.60-2.64 tons/ha. The carbon content in the soil ranges from 8.66-156.83 tons/ha with an absorption capacity of 31.79-575.55 tons/ha. This study can be used as basic data in future policies for climate change mitigation, especially the mangrove ecosystem in Sinjai Regency, South Sulawesi Province and can open up opportunities for carbon-based economic schemes such as carbon trading.